Association of genetic variants of the chemokine receptor CCR5 and its ligands, RANTES and MCP-2, with outcome of HCV infection. - Hellier, S; Frodsham, A; Hennig, B; Klenerman, P; Knapp, S; Ramaley, P; Satsangi, J; Wright, M; Zhang, L; Thomas, H; Thursz, M; Hill, A (2003)
The effect of host genetic variation on the outcome of hepatitis C virus (HCV) infection and its treatment is poorly understood. The chemokine receptors CCR5, CCR2, and CCR3 and their ligands, RANTES, MCP-1, MCP-2, and MIP-1alpha, are involved in the immune responses and the selective recruitment of lymphocytes to the liver in HCV infection. We studied 20 polymorphisms within these genes and investigated their association with persistent carriage of HCV, severity of liver disease, hepatic inflammation, and response to treatment in a large European cohort. Significant associations were found between CCR5-delta32 and reduced portal inflammation (P =.011, odds ratio [OR]: 2.3, 95% confidence interval [CI]: 1.09-4.84) and milder fibrosis (P =.015, OR: 1.97, 95% CI: 1.13-3.42). A promoter polymorphism at position -403 in the RANTES gene was associated with less severe portal inflammation (P =.004). An amino acid change in MCP2, Q46K, was associated with severity of fibrosis (P =.018, OR: 2.29, 95% CI: 1.14-4.58). In conclusion, our study suggests a possible role of the polymorphisms CCR5-delta32, RANTES -403, and MCP-2 Q46K in the outcome of HCV infection.